2019
DOI: 10.3390/cells8101153
|View full text |Cite
|
Sign up to set email alerts
|

TGR5 Activation Modulates an Inhibitory Effect on Liver Fibrosis Development Mediated by Anagliptin in Diabetic Rats

Abstract: Hyperglycemia and hyperinsulinemia activate the proliferative potential of hepatic stellate cells (HSCs) and promote hepatic fibrosis. Dipeptidyl peptidase-4 (DPP-4) inhibitors, antidiabetic agents, reportedly inhibit the HSC proliferation. Additionally, Takeda G protein-coupled receptor 5 (TGR5) agonists induce the systemic release of glucagon-like peptides from intestinal L cells, which maintains glycemic homeostasis. This study assessed the combined effect of TGR5 agonist and DPP-4 inhibitor on diabetes-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Of 47 rodent studies, 30 (63.8%) studies were conducted in mice ( 35 41 , 44 46 , 48 , 52 , 53 , 55 , 56 , 59 65 , 68 , 70 , 74 79 ) and the others were in rats ( 5 , 6 , 42 , 43 , 47 , 49 51 , 54 , 57 , 58 , 66 , 67 , 69 , 71 73 ). Their characteristics, housing, acclimatization, and diet treatments were presented in Table 3 and Supplementary Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Of 47 rodent studies, 30 (63.8%) studies were conducted in mice ( 35 41 , 44 46 , 48 , 52 , 53 , 55 , 56 , 59 65 , 68 , 70 , 74 79 ) and the others were in rats ( 5 , 6 , 42 , 43 , 47 , 49 51 , 54 , 57 , 58 , 66 , 67 , 69 , 71 73 ). Their characteristics, housing, acclimatization, and diet treatments were presented in Table 3 and Supplementary Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…It was previously reported that TGR5 expression, which is very low in quiescent HSCs, is upregulated during the activation of HSCs into a myofibroblast-like phenotype [4,26]. Thus, stimulation of TGR5 on activated HSCs may contribute to the beneficial effects of oleanolic acid on fibrosis development in the above model [58]. Furthermore, mice deficient in both TGR5 and the nuclear bile acid receptor FXR were generated and showed an enrichment in gene expression pathways associated with liver fibrosis and inflammation in line with our study [59].…”
Section: Discussionmentioning
confidence: 99%
“…Through modulation of PDGFRβ expression, it may also contribute to the response of HSCs to microvascular thrombosis and platelet-derived signals. A recent study explored the effect of the non-bile acid TGR5 ligand oleanolic acid in a rat model of liver fibrosis development [58]. Treatment with oleanolic acid significantly reduced fibrogenesis in vivo; however, a direct effect on HSCs in vitro was not observed, since the cell lines used did not express TGR5 [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings show the complexity of TGR5 signaling in the pathogenesis of liver fibrosis. The complexity of this pathway is further documented by Kaya et al demonstrating that the TGR5 agonist oleanolic acid significantly improved glycemic status and attenuated intrahepatic steatosis in male diabetic rats that received intraperitoneal injections of porcine serum to induce liver fibrosis [12]. Interestingly, the authors found that the TGR5 agonist oleanolic acid inhibited the increase in the Firmicutes/Bacteroidetes ratio that is an indicator of dysbiosis related to metabolic syndromes.…”
Section: Bile Acids In Hepatic Fibrosismentioning
confidence: 90%